Etching Techniques on Airborne-Particle Surface Treated Cast Postand Fiber Posts - Desai, Aarti; Karkera, Reshma; R. Shetty, Deeksha; Riyan , Mohammed; Raj, Pushp; Bhide, Manasa (Journal of Neonatal Surgery, 2025)
In order to produce surface roughening, studies have shown that airborne particle abrasion is applied, allowing materials to have increased bonding capabilities. Therefore the aim was to assess the effect of etching techniques on surface treated with cast & fiber posts. 48 freshly extracted mandibular 1st pre molar were divided into 3 groups I, II & III with 16 samples each , which was further sub-divided into 2 groups a & b with 8 samples each. We found that, ANOVA test , Turkey HSD test and T test showed significance for both the groups & subgroups, except , I(a) with III(a) and I(b) with III(b) and II(a) with II (b) respectively. Post spacing significantly increased the binding strength of fiber posts cemented.